Niveles de promotores de crecimiento en la alimentación de cuyes mejorados (Cavia porcellus L.) en la etapa de crecimiento y engorde en el cantón Salcedo - Fernández Ampudia, Carmita Patricia (2013)
This research was executed in the province of Cotopaxi to the North - East of the Salcedo Canton at 1 km from the urban sector via NavasRumipambafarm Primavera 4 owned by Mr. Miguel Aguilar. The field investigation was 10 weeks. Assessed the inclusion of the promoter of growth Sel-Plex in the diet of improved guinea pigs (Caviaporcellus l.) where the factors in study were sex (male and female) and levels of the promoter (0, 0.1, 0.2 and 0.3 ppm of Sel-Plex). The experimental design used was the 4n factorial arrangement * 2s, with design BCA (random complete blocks) with eight treatments each and 3 experimental units; with three replicates, where the "s" factor corresponds to the sex of the animals and the "n" factor to the levels of natural promoter of growth Sel-Plex. In the interactions of sex by levels of Sel-Plex of food consumption can be seen in female sex reflects interaction 42 and 56 days with level 0.3 ppm of Sel-Plex with 5696.99 and 5856.24 (g). The weight gain of the interactions of sex by level of Sel-Plex can be seen that in the male Guinea Pigs their interaction is 14 and 28 days with level 0.3 ppm of Sel-Plex with 162.00 159.00 and (g). The interactions of sex by levels in feed conversion can be seen in that 14 and 28 days there interaction was the Guinea Pigs females with the level 0.2 ppm of Sel-Plex with 4.20 and 4.29. In the performance at the channel 6 treatment with1195 (g); in the carcass weight results in average is for 6treatment with 941 (g).